Stolen wealth, perpetrators and punishments in Moldova (17th century – early 18th century) - Chelcu, Cătălina (Balcanica Posnaniensia. Acta et studia, 2020)
For the historical period we refer to, no proper inventories have been made containing the unjustly appropriated goods. They are just mentioned as such or listed, if that was the case, according to the size of the damage. There are also documentary sources in which the object of the theft is less represented, the justice system focusing in those cases rather on the wrongdoers, than on the wrong actions. That is why, the blood money “paid for some reason”, with no other specific details, is quite frequently cited. Rare or frequent, these documents are complaints addressed by the victim to the Prince and his officials, documents in which the perpetrators admitted their fault, or deeds issued by the judicial authority subsequent to the investigation of the criminal act. In discussing the theft of/from the wealth, i.e. from the whole amount of the available goods, we are interested in clarifying some aspects pertaining to a reality that the historian should reconstruct, with all the complexity of its evolution: the motivations of the theft and its circumstances, the types of theft, the social categories involved, the time and space of the misdemeanour, the perpetrators’ punishment. Briefly, the study is about starting to write a history of the reprehensible acts liable to punishments for theft and robbery in 17th and early 18th century Moldavia.